Seasonal cooling load reduction of building by thermosyphon heat pipe radiator in different climate areas - Chotivisarut N. (2017)
In this study, a concept of using thermosyphon heat pipe radiator to extract heat from water in a storage tank to generate cooling water during the nighttime was proposed. The cooling water could be used to serve the cooling load in a room during the daytime. A tested room with artificial load was constructed and a heat transfer model to calculate the water temperature during the nighttime and the room temperature during the daytime was developed. The simulated results agreed well with those of the experimental data. The model was used to find out the possibility of this concept for seasonal cooling load reduction of the similar building in the areas of different climates. The selected sites were Bangkok and Chiang Mai, Thailand and also Alice Springs, Australia where they are hot and humid, hot and semi-humid, and hot and semi-arid, respectively. Cooling water was produced during winter and used to serve cooling load in an air-conditioned building in summer. It found that, among three cities, Alice Spring showed a highest potential followed by Chiang Mai and Bangkok. The effect of controlled room temperature and UA of the room cooling coil on summer load fraction were shown. © 2011 Elsevier Ltd.